A Modern Review of Hindu Dharma - Nandhikkara, Jose (Journal of Dharma, 1975)
The term Dharma has been one of the most powerful and influential terms in Indian thought and society for several millenia, dating from Vedic times. Even today it is very influential at all levels of society and among all classes, castes, and creeds. However, there are diverse ways in which the term has been used. It stands for religious observance, righteousness, jsutice, conformity to law, conformity to custom, obedience to the social roder, sense of duty, etc. Thus, it has religious, moral, ethical as well as legal significance. This is one of the important reasons why it is impossible to translate the term Dharma to any other non-Indian langugae.